Variability of Neuronal Responses: Types and Functional Significance in Neuroplasticity and Neural Darwinism - Chervyakov, Alexander V.; Sinitsyn, Dmitry O.; Piradov, Michael A. (Frontiers in Human Neuroscience, 2016)
In many cases, neural signals detected under the same external experimental conditions significantly change from trial to trial. The variability phenomenon, which complicates extraction of reproducible results and is ignored in many studies by averaging, has attracted attention of researchers in recent years. In this paper, we classify possible types of variability based on its functional significance and describe features of each type. We describe the key adaptive significance of variability at the neural network level and the degeneracy phenomenon that may be important for learning processes in connection with the principle of neuronal group selection.